2018
DOI: 10.1016/j.jval.2018.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Patient-Reported Outcome Measures in the Food and Drug Administration Pilot Compendium: Meeting Today’s Standards for Patient Engagement in Development?

Abstract: For the FDA Pilot COA Compendium to fulfill its purpose of fostering PFDD, it needs fine-tuning to reflect today's standards, improving transparency and facilitating clear identification of included measures so that the level of patient engagement, among other factors, can be properly assessed. Suggested improvements include identifying clinical trials that correspond to the COA Compendium's use in drug development; more clearly identifying which measure is referred to; and including only those measures that a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…This use of the RDQ has increased substantially over the last 5 years of our review which may be a reaction to regulatory pressure to incorporate patient assessments for drug, surgical technique, and device approval. 25 Other frequently used PROs in esophageal disease, such as the Eckardt score, are not formally validated but are widely included in studies as a means to compare treatment response. 26,27 Nonetheless, despite the apparent enthusiasm for using the RDQ in this fashion, it precludes an accurate comparison across study responses since they are self-referential.…”
Section: Discussionmentioning
confidence: 99%
“…This use of the RDQ has increased substantially over the last 5 years of our review which may be a reaction to regulatory pressure to incorporate patient assessments for drug, surgical technique, and device approval. 25 Other frequently used PROs in esophageal disease, such as the Eckardt score, are not formally validated but are widely included in studies as a means to compare treatment response. 26,27 Nonetheless, despite the apparent enthusiasm for using the RDQ in this fashion, it precludes an accurate comparison across study responses since they are self-referential.…”
Section: Discussionmentioning
confidence: 99%
“…PFDD has become a more common practice. Although the FDA has developed five regulatory guidance's on PFDD, 7,8 there is still room to grow when it comes to the level of industry adoption and patient participation. The FDA posts Voice of Patient reports on their website for all patient‐focused drug development meetings 9 which are a valuable resource for regulatory review of new drugs.…”
Section: Power Of the Patient Voicementioning
confidence: 99%
“…This is the razors edge I live… I shared with the FDA that my priority of needs was (1) to slow progression and prolong my surgical benefits for as long as I could, (2) treat (and educate society) the constellation of non-motor symptoms (NMS), (3) recognize the shortcomings of existing medications, (4) identify patients earlier so as to really make an impact, and ( PFDD has become a more common practice. Although the FDA has developed five regulatory guidance's on PFDD, 7,8 there is still room to grow when it comes to the level of industry adoption and patient participation. The FDA posts Voice of Patient reports on their website for all patient-focused drug development meetings 9 which are a valuable resource for regulatory review of new drugs.…”
Section: Parkinson's Patient Reflection: Then and Nowmentioning
confidence: 99%
“…Even though the sensory texture may be predicted from instrumental assessments, such inferences can be debated or interpreted differently in the absence of sensory data. In most human clinical studies, Patient-Reported Outcome Measures (PROs) through interviews and questionnaires 32 were used to infer the acceptability of food texture. Although informed by bioethics, we highlight the potential limitations of these approaches and make appraisals for potential improvements.…”
Section: Reviewmentioning
confidence: 99%
“…Research on nutrition in HNC patients has focused significantly on how alterations in oral and swallowing systems affect the ability of patients to consume certain food textures, compromise food intake, and nutritional status (Table 3). The studies are based on clinical findings, systematic observations, interviews and self-reported questionnaires (Clinical Outcome Assessment (COA) through Patient-Reported Outcome Measures (PROs) 32 ), as well as on the objective instrumental assessment of oral physiology. Using the EAT-10 (the Eating Assessment Tool) questionnaire, Morioka et al 84 found that oral dysfunction negatively affected nutritional status in HNC patients via food texture-related mechanisms.…”
Section: Food Texture In Altered Oral Functionmentioning
confidence: 99%